5

Consider the following argument:

Turtles see everything. Seeing is asymmetric (for the sake of argument). Therefore, something is not a turtle.

I have problems symbolizing these statements.

My attempt:

**Predicates:**

Tx: x is a turtle

Sxy: x sees y

**Premises:**

1) (∃xTx) Λ ∀x∀y(Tx → Sxy)

2) ∀x∀y (Sxy → ¬Syx)

Using this set-up I cannot deduce the conclusion, which is ∃x¬Tx.

I feel like my set-up is wrong. I think I should be able to complete the proof after correctly symbolizing the statements. Please let me know how to proceed.

1Isn't ths a take on Rissell's paradox? – Richard – 2019-03-02T11:30:19.303

I think in the second premise, you're taking the converse instead of the contrapositive. Asymmetric doesn't mean that the reverse is always untrue. – luser droog – 2019-03-02T21:28:33.623